Differences in the inflammatory response and outcome among hospitalized patients during different waves of the COVID-19 pandemic - Briciu, Violeta; Leucuta, Daniel-Corneliu; Muntean, Monica; Radulescu, Amanda; Cismaru, Cristina; Topan, Adriana; Herbel, Lucia; Horvat, Melinda; Flonta, Mirela; Calin, Mihai; Dobrota, Roxana; Lupse, Mihaela (Frontiers in Immunology, 2025)
IntroductionThe aim of this study was to evaluate differences in inflammatory biomarkers and their association with outcomes in hospitalized patients with coronavirus disease 2019 (COVID-19) during four pandemic waves determined by different SARSCoV- 2 variants of concern. We explored if laboratory biomarkers of inflammation adjusted to patients’ comorbidities, age, and vaccination status correlated with severity and mortality.MethodsA retrospective study on 8,614 consecutive hospitalized COVID-19 patients was conducted in a Romanian hospital on a 3-year interval (February 2020 to May 2023). Data collected included demographics, duration of hospitalization, comorbidities, vaccination status, COVID-19 severity, outcome, and markers of inflammation from the first blood test performed at admittance [C-reactive protein (CRP), fibrinogen, ferritin, lactate dehydrogenase (LDH), procalcitonin (PCT), IL-6, D-dimer, and complete blood count]. Systemic inflammatory indexes like neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocyte ratio (dNLR), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), neutrophil-to-platelet ratio (NPR), Systemic Immune-Inflammation Index (SII), and systemic inflammation response index (SIRI) were calculated.ResultsThe Delta wave, characterized by the longest hospitalizations and the highest rates of severe cases and mortality, showed significant elevations in inflammatory biomarkers. CRP, fibrinogen, ferritin, IL-6, D-dimer, and LDH increased in their median values from the Wuhan to Delta wave and decreased in the Omicron wave, except PCT, which increased from the Alpha to Omicron wave. Leukocytes and neutrophils increased in their median values from the Wuhan to Delta wave and decreased in the Omicron wave, while an inverse pattern can be observed for lymphocytes, monocytes, and basophils. The best inflammatory biomarkers for predicting severe/critical COVID-19 were CRP, dNLR, LDH, and NLR (cut-off of 3.41 mg/dL, 3.05, 262 U/L, and 4.5, respectively), while for predicting death outcomes, the best biomarkers were dNLR, NLR, LDH, and NPR (cut-off of 3.6, 4.9, 278 U/L, and 0.02, respectively). For all these biomarkers, the areas under the curve (AUCs) surpassed 0.8. In the multivariate analysis, the highest adjusted OR for death was described for dNLR (8.46), NLR (7.59), LDH (5.99), and NPR (5.5), while increased lymphocytes decreased the highest adjusted OR for death (0.16).ConclusionThe study, underscoring the dynamic nature of COVID-19, brings a detailed analysis of biomarker trends that could provide valuable information for the early identification of patients at risk for severe outcomes, allowing for timely interventions.